Rethinking Assessment in an Indigenous Specific Program - Fleet, Alma; Kitson, Rosalind (Alberta Journal of Educational Research, 2010)
Nonstandard entry programs into higher education include worthy goals and problematic processes. Although effective practices in teacher education would seem to be well established, complications arise when good intentions intersect with university protocols, issues of power, history, rights, and cultural complexities. This article reports on an Australian study on assessment approaches in an early childhood Indigenous teacher education program. Focus group investigations with current students and teaching staff and interviews with graduates reveal some similarities in perception, but a range of challenges to be addressed. Diversity of perspective characterizes both the student groups’ and lecturers’ responses.